Exploring Media-Based Interventions for Adolescent Mental Health: Literature Review - Choirunissa, Risza; Nugraheni, Sri Achadi; Purnami, Cahya Tri; Wahyuningsih, Nur Endah (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Media-based interventions show promise in addressing the rising mental health concerns among adolescents, surpassing challenges associated with traditional care. This review critically assesses the effectiveness of media-based interventions in promoting adolescent mental health, with a specific focus on social media, digital applications, and film. The methodology employs a comprehensive approach, utilizing Google Scholar, Scopus, and PubMed databases (2012-2022) with keywords such as "mental health," "media," and "adolescents." the methodology is refined for enhanced clarity, explicitly detailing the search strategy, inclusion and exclusion criteria, and selection process. Findings from the analysis of 13 selected articles highlight promising outcomes of digital interventions in screening and treating mental disorders in adolescents. Emphasizing scalability, accessibility, and personalization benefits, the review recognizes the importance of addressing privacy concerns and the potential drawbacks of relying solely on digital platforms. Additionally, it emphasizes the impact of using booklets for mental health self-management in schools. The review improves organization and flow, eliminating repetition for a clearer presentation of information, providing a detailed evaluation of their strengths and limitations, enhancing the overall credibility of the review. the abstract explicitly discusses limitations related to inclusion criteria, such as language restrictions and the exclusion of specific study designs. This comprehensive approach contributes to a more robust understanding of the literature, providing valuable insights for researchers, practitioners, and policymakers involved in developing effective interventions for adolescent mental health. The implications stress the need for further research, evidence-based intervention development, and considerations for implementation and user experience in digital interventions.